The study of humic acid foliar application on physiological and biochemical changes in wheat under irrigation withholding at different growth stages - Tohidi, HR (International Journal of Natural Sciences, 2016)
In order to study effect of humic acid (HA) foliar application and limited irrigation, on physiological and biochemical characteristics of wheat an experiment was conducted in research field of Varamin, Iran during 2012 growing season. The experimental design was laid out in a randomized complete block with a split plots arrangement of treatments in three replications. Main plots included four different levels of irrigation (complete irrigation, irrigation withholding at stem elongation stage, irrigation withholding at flowering stage and irrigation withholding at seed setting stage) and three different concentration of HA foliar application (0, 150 and 300) was allocated to subplots. The results showed that irrigation withholding conditions in different growth stages significantly decreased seed yield and total chlorophyll content but by contrast increased electrolyte leakage, antioxidant enzymes activity and lipid and protein peroxidation. It appears that HA act in plants via a specific form of stress that is detected by anti-stress defense systems in plants. These HA applied to plants can protect against water stress in degraded soils. International Journal of Natural Sciences (2015), 5(1) 1-7